Literature Review: Analisis Efikasi ESWL sebagai Tatalaksana Nefrolitiasis - Yana Mastionita Br Damanik; Eka Yudha Rahman; Istiana Istiana (Homeostasis, 2021)
Abstract: Extracorporeal Shockwave Lithotripsy (ESWL) is the first-line treatment for nephrolithiasis which is minimally invasive with a clearance rate of 85.3%. In its implementation, ESWL is influenced by many factors, which make many variations in its effectiveness. The literature review aims to analyze the efficacy of ESWL to treat nephrolithiasis in terms of age, sex, size and location of stones. Writing is done by analyzing related journals obtained through a database of medical journals, namely PubMed, Google Scholar, Cochrane, and DOAJ. Journals in English with publication time of 2006-2020, a total of 13 journals were obtained. The results consisted of the highest ESWL efficacy level, stone size = 6 mm (93.6%), stone location (upper calyx) by 100%, women (90.3%), men (85.5%), ages 31- 40 years (89%) . The lowest level of efficacy obtained related to the factors studied was stone size> 15 mm (54.9%), stone location (lower calyx) by 30.81%, women (66%), men (78%). and aged ≤ 65 years (69.2%). The conclusion was that stone size and stone location tended to affect the efficacy of ESWL (p <0.05) while age and sex tended not to affect efficacy (p> 0.05). Keywords: nephrolitiasis, efficacy factor, ESWL Abstrak: Extracorporeal Shockwave Lithotripsy (ESWL) menjadi first-line treatment nefrolitiasis yang bersifat minimally invasive dengan clearance rate 85.3 %. Dalam pelaksanaannya, ESWL dipengaruhi oleh banyak faktor, yang membuat banyak variasi keefektifannya. Literature review bertujuan menganalisis efikasi ESWL sebagai tatalaksana nefrolitiasis terkait faktor usia, jenis kelamin, ukuran dan lokasi batu. Penulisan dilakukan dengan menganalisis jurnal terkait yang didapatkan melalui database jurnal kedokteran, yaitu PubMed, Google Scholar, Cochrane, dan DOAJ. Jurnal dalam bahasa Inggris dengan waktu publikasi 2006-2020, total didapatkan 13 jurnal. Hasil berupa tingkat efikasi tertinggi ESWL secara berurutan, ukuran batu =6 mm (93.6%), lokasi batu (kaliks atas) sebesar 100 %, wanita (90.3%), pria (85.5%), usia 31- 40 tahun (89%). Tingkat efikasi terendah yang didapat terkait faktor yang diteliti adalah ukuran batu >15 mm (54.9%), lokasi batu (kaliks bawah) sebesar 30.81 %, wanita (66%), pria (78%). dan usia ≤ 65 tahun sebesar (69.2 %). Kesimpulan didapatkan bahwa ukuran batu dan lokasi batu cenderung mempengaruhi efikasi ESWL (p<0.05) sedangkan usia dan jenis kelamin cenderung tidak mempengaruhi efikasi (p>0.05). Kata-kata kunci: efikasi, faktor efikasi, ESWL